2019
DOI: 10.1155/2019/6507286
|View full text |Cite
|
Sign up to set email alerts
|

Sterilisation in Dentistry: A Review of the Literature

Abstract: In a small and medium-sized dental facility, the correct management of the sterilisation and presterilisation phases plays a fundamental role in good management of instruments and personnel, in order to ensure conditions that are more efficient with less down time. Nowadays, instrument sterilizers are increasingly efficient in achieving results, both in terms of time and size, and ensure that materials are sterile and ready to be stocked in a reasonable time. A literature search for articles related to revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 36 publications
0
38
0
7
Order By: Relevance
“…Depending on the phase of treatment, endodontic instruments are divided into instruments for probing the endodontic canal for the pre-enlargement, and glidepath for shaping the canal or instruments for the closure and three-dimensional sealing of endodontic canals [1,2]. Many of these tools are reusable after performing cleaning, disinfection, and sterilization procedures by autoclaving [3].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the phase of treatment, endodontic instruments are divided into instruments for probing the endodontic canal for the pre-enlargement, and glidepath for shaping the canal or instruments for the closure and three-dimensional sealing of endodontic canals [1,2]. Many of these tools are reusable after performing cleaning, disinfection, and sterilization procedures by autoclaving [3].…”
Section: Introductionmentioning
confidence: 99%
“…Autoclaving has always been considered the best method of sterilization for dental instruments. 10,11 At the sterilization chamber the steam is introduced at a very high pressure and temperature, 11 In order to study the effect of this physical challenges on the used rubber tips, studies of the plasticity * and Plasticity Retention Index (PRI) ** of silicon rubbers and other elastomers found that the long term performance of silicones is generally excellent. Although exposure to steam at high pressure, as well as ageing in closed systems can lead to degradation via a hydrolysis reaction, 12 decreasing their PRI.…”
Section: D) Disinfection and Sterilization Protocolmentioning
confidence: 99%
“…Методи стерилізації поділяються на механічні, фізичні та хімічні. [15], кожний з яких має переваги та недоліки, відтак єдиного універсального методу немає. У стоматологічній практиці методи комбінують, використовуючи для кожного об'єкту «свій» найбільш прийнятний.…”
Section: вступunclassified